Can user involvement, training and internal control improve information system performance? - Astuti, Fitri; Nusron, Lulu Amalia; Khamainy, Arief Hidayatullah (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2022)
Abstract The implementation of technology is a driving force for performance in both the private and government sectors. Several researchers have examined various factors that influence technology implementation with mixed results. The purpose of this study was to explore the effect of user involvement, education & training programs, and internal control sistems on the performance of the village financial sistem (Siskeudes). The respondents of this study were 110 village officials who used the village financial sistem. This study used the purposive sampling technique to obtain data from 17 sub-districts in Bantul Regency. Analysis of data validity using Pearson correlation and data reliability analysis using Cronbach's alpha. The test results using multiple regression analysis show that user involvement, education and training programs, and internal control sistems affect the village financial sistem. This research implies that the government needs to increase the expertise of the apparatus in using information technology to accelerate the presentation of financial reports in the village. Keywords: Education and training programs; internal control sistem; and user involvement; village financial sistem.